1987
DOI: 10.3382/ps.0660802
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Major Histocompatability Complex on Disease Resistance and Productivity

Abstract: Publications in which chickens of different B haplotypes were studied for differences in disease resistance or productivity traits are reviewed. The most prominent effects on diseases are those involving tumors, but other examples involving autoimmune disease and microbial infections not resulting in neoplasia or autoimmunity are also cited. Each referenced disease paper is briefly defined with regard to: population used, B alleles present, and the most resistant B types. Studies citing B haplotype influences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
98
2
2

Year Published

1990
1990
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(109 citation statements)
references
References 35 publications
7
98
2
2
Order By: Relevance
“…Our results from lines XP02 and XP21 confirm the resistance of the B2i haplotype (XP21) and B 2 haplotype (XP02) against multiple MD viral strains (Gavora et al, 1986;Bacon 1987 In the determination of the PHA swelling index, possible differences in wing web thickness of the right and left wing or the variation in the response to PBS were not considered as it was shown that they are negligible (Van der Zijpp, 1983).…”
Section: Introductionsupporting
confidence: 51%
“…Our results from lines XP02 and XP21 confirm the resistance of the B2i haplotype (XP21) and B 2 haplotype (XP02) against multiple MD viral strains (Gavora et al, 1986;Bacon 1987 In the determination of the PHA swelling index, possible differences in wing web thickness of the right and left wing or the variation in the response to PBS were not considered as it was shown that they are negligible (Van der Zijpp, 1983).…”
Section: Introductionsupporting
confidence: 51%
“…The major histocompatibility complex (MHC) B alleles have been found to play a major role in resistance to AL viraemia and tumour development (Bacon, 1987). A link between MHC genotype and the risk of becoming a virus shredder has also been reported (Yoo and Sheldon, 1992).…”
Section: Avian Infectious Bronchitismentioning
confidence: 99%
“…This strain of chickens was chosen for its high susceptibility to MD (Longenecker & Mosmann, 1981;Bacon, 1987).…”
Section: Chickensmentioning
confidence: 99%